1977
DOI: 10.1111/j.1365-2621.1977.tb08437.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Meat Pieces: A Comparison of Myosin, Actomyosin and Sarcoplasmic Proteins as Binding Agents

Abstract: Suspensions of myosin, actomyosin and sarcoplasmic protein, isolated from beef semitendinosus muscle, were prepared at several protein concentrations and with various amounts of added sodium chloride up to 1.4M. An aliquot from each suspension was pressed between two pieces of muscle of fixed cross‐sectional area and cooked. Binding strength was estimated from the force required to separate the meat pieces. At salt concentrations up to 1M the binding strength of myosin was superior to that of actomyosin (P = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(62 citation statements)
references
References 15 publications
2
59
0
Order By: Relevance
“…24 ) In contrast, this investigation with cardiac myosin and reconstituted acto-myosin complexes suggests that myosin alone forms stronger heat-induced gels than actomyosin does. This partly agrees with the observation of Macfarlane et al 6 ) who reported a higher binding power of myosin than that of actomyosin. In previous studies with skeletal muscle actin-myosin complexes, the strongest gels were produced at.…”
Section: Ultrastructural Features Of the Gelsupporting
confidence: 82%
“…24 ) In contrast, this investigation with cardiac myosin and reconstituted acto-myosin complexes suggests that myosin alone forms stronger heat-induced gels than actomyosin does. This partly agrees with the observation of Macfarlane et al 6 ) who reported a higher binding power of myosin than that of actomyosin. In previous studies with skeletal muscle actin-myosin complexes, the strongest gels were produced at.…”
Section: Ultrastructural Features Of the Gelsupporting
confidence: 82%
“…
IntroductionFunctional properties of heat-induced myofibrillar protein gel were important for meat products (Fukazawa et al, 1961;Macfarlane et al, 1977;Siegel and Schmidt, 1979). Gel formation was typically induced by association of unfolded protein molecules via various chemical forces, namely disulfide linkages, electrostatic, hydrophobic interactions, and hydrogen bonds (Mulvihill and Kinsella, 1987;Oakenfull et al, 1997).
…”
mentioning
confidence: 99%
“…Helicity corresponding to the reduced mean residue rotation at 233 nm ([m ' h33) was calculated as described by Samejima et al 23 ) Measurements ofgel strength. Heat-induced gel strength (rigidity) of myosin was estimated by the method of Yasui et al2 4 ) Other conditions (ionic strengths, pH, protein concentrations, temperature) are defined at appropriate places in the text.…”
Section: Methodsmentioning
confidence: 99%